Sociodemographic, biological, psychological, and behavioral correlates of cycling in community-dwelling Japanese older adults: A cross-sectional study - Shiho Amagasa; Noritoshi Fukushima; Hiroyuki Kikuchi; Yumiko Ohya; Yuko Odagiri; Tomoko Takamiya; Koichiro Oka; Yoshinori Kitabatake; Shigeru Inoue (Japanese Society of Physical Fitness and Sports Medicine, 2017)
Cycling is a way for older adults to be physically active and remain healthy. This descriptive epidemiological study investigated the role of sociodemographic, biological, behavioral, and psychological correlates associated with cycling among community-dwelling older adults in Japan. This cross-sectional study, conducted in 2010, included 1,938 community-dwelling older adults aged 65 to 74 years, from three cities in Japan: Bunkyo City (urban area) and Fuchu City (suburban area) in Tokyo, and Oyama City in Shizuoka (rural area). Participants were randomly selected from resident registries and a questionnaire was mailed to each one (response rate of 75.7%). All data was self-reported, including cycling time. Multivariable logistic regression analysis was used to calculate the adjusted odds ratios (ORs) and 95% confidence intervals (CIs) for cycling. The proportion of men and women who cycled was 30.1% and 28.3%, respectively. Cycling was strongly associated with residential area: in men, Fuchu (suburban) (ORs = 3.15, 95% CIs = 2.20-4.52), Oyama (rural) (0.14, 0.08-0.25); in women, Fuchu (suburban) (4.15, 2.80-6.16), Oyama (rural) (0.21, 0.11-0.40), compared to Bunkyo (urban). Moreover, cycling was inversely associated with being underweight (0.26, 0.08-0.80) in men; for women, it was inversely associated with living alone (0.51, 0.29-0.90) and with not working (0.56, 0.38-0.84), and positively associated with not driving often (2.81, 1.47-5.40), and with not possessing a driver's license (2.16, 1.23-3.79). The prevalence of cycling among older adults is relatively high in Japan. However, it varies greatly depending on residential area. Differences in residential areas may be taken into account to promote effective strategies for cycling.